Tindakan Menguasai Pasar Luar Negeri Secara Illegal (Analisis Pengenaan Bea Masuk Anti Dumping Terhadap Impor Produk Hot Rolled Plate (HRP) Dari Negara Republik Rakyat Tiongkok (RRT), Ukraina, dan Singapura) - Arifin Ma’ruf (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2017)
The results of the study show that, in Article 6 paragraph (2) PP. 34 of 2011on Antidumping Measures, Measures of Action, and Safeguard Measures Tradestipulates that investigation requests can not be made when the dumping margin is lessthan 2%. Based on PMK Regulation No. 150 / PMK.011 / 2012 dated October1, 2012 the amount of anti-dumping duties for PRC 10.47%, Singapore 12.33%and Ukraine 12.50%. Referring to the above regulation of imposition of anti-dumpingduties for Singapore and Ukhrainian PRC is appropriate, because the findings ofmargin dumping already exceed 2%.